Studi komparasi Regulasi Sertifikasi Produk Halal Antara Indonesia dan Malaysia - Muhammad Abdurrahman Shalahuddin; Khairul Fitroh; Ruli Margianto (Journal of Fiqh in Contemporary Financial Transactions, 2024)
This study aims to determine the history of halal certification regulations in Indonesia and Malaysia and to compare the regulations of the two countries related to halal product certification. The method used in this research is normative juridical method with a comparative approach. The results of the study explain first the history of halal product certification regulations in Indonesia and Malaysia marks legal changes to ensure compliance with Islamic halal principles. Indonesia, through the JPH Law and the establishment of BPJPH, adopts an integrated approach, while Malaysia uses a layered approach with APD 2011, involving external agencies such as JAKIM and HDC. The halal certification processes in Indonesia and Malaysia differ in approach, regulatory structure, and institutions involved. Indonesia applies an integrated approach through BPJPH, while Malaysia uses a layered approach with APD 2011. Although different, both have similar objectives in ensuring compliance with Islamic halal principles and protection of Muslim consumers, as well as efforts to be in line with recognized international standards.